Exploration and research on the paradigm of innovative culture construction in local university computer laboratories and equipment - Li, Dawei; Lu, Junjie; Huang, Zixin (Frontiers in Education, 2025)
IntroductionThe culture of computer laboratories and equipment in universities is an important component of university culture. Strengthening the construction of laboratory and equipment culture is an inevitable requirement for implementing the goal of moral education, improving the level of experimental teaching, and innovating scientific research achievements.Methods(1) Integrating ideological and political elements into experimental teaching content to enrich students' moral and professional development; (2) Introducing a new teaching model “learning competition conjugation” to modernize equipment usage and stimulate innovation; (3) developing an open practical education platform based on the integration of science and education; and (4) establishing a science popularization education platform to inspire creativity and broaden scientific thinking.ResultsEnhanced students' professional skills, ideological awareness, and creativity. Laboratory usage became more dynamic, with improved teaching effectiveness and interdisciplinary collaboration.DiscussionStrengthening laboratory culture through ideological integration and innovative teaching fosters a more open, holistic, and creative academic environment, offering practical guidance for university reforms.